The Influence of Brand Image Brand Awareness and Promotion on Purchase Decisions for Ubiquiti Brand IT Network Devices in Indonesia - Axel Orlen Rondonuwu; Freddy Rangkuti (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
The background of this research is the increasing demand and competition in the wireless network device industry. Ubiquiti, as one of the major players in the industry, needs to understand how brand image, brand awareness, and promotional activities influence consumers' purchasing decisions. This study aims to analyze the influence of brand image, brand awareness, and promotion variables on purchasing decisions on Ubiquiti brand IT network products. Data were collected from 97 respondents, and analysis was conducted on the demographics of respondents, product use, and the influence of independent variables on purchasing decisions. Research analysis method using SPSS. The results showed that the majority of product users were men aged 25-29 years who worked as employees and used the product for less than 1 year. Statistical analysis revealed that the three variables of brand image, brand awareness, and promotion significantly influence purchasing decisions. Brand awareness has been shown to have the most influence, followed by brand image and promotion. This finding is reinforced by brand awareness's largest adjusted R square value (96.8%). The main conclusion is that brand awareness has the most significant influence on consumer purchasing decisions Ubiquiti brand IT network products, followed by brand image and promotion. The implication of this study is the importance of companies in designing effective marketing and branding strategies to improve consumer purchasing decisions. The research provides valuable insights for Ubiquiti and other companies in the wireless networking industry to better understand the factors driving consumer buying behavior, so they can develop targeted marketing strategies and increase their market share.